Metais dissolvidos no sistema estuarino Piraquê-Açu e Piraquê-Mirim e a composição geoquímica de rochas e solos da bacia hidrográfica adjacente, Aracruz-ES - Rodrigues, Dehan Regis Poli (2017)
The concern for the environment has arisen expressively for a few decades, taking on new dimensions in the world scene, as well as in the various sectors of society. Although estuaries are new environments in geologic time, it is of great economic and environmental importance. Metallic elements found in river basins, rivers and estuaries generally have natural sources, but anthropic factors may also contribute specifically to estuaries in more urbanized river basins. The study area includes the Piraquê-açu - Piraquê-mirim (SEPAPM) estuarine system, located in the district of Santa Cruz, 60 km from the capital of the Espírito Santo State, Vitória. The objective of this work was to evaluate the sources and variations in the concentrations of major (Al, Fe and Mn) and trace (Zn, Cr, Ni, As, Pb and Ni) dissolved elements in the SEPAPM considering the climatic variations, hydrodynamic processes, as well as the rocks and soils of the adjacent watershed. 42 soil samples and 26 rock samples were collected in the SEPAPM watershed for analysis. Water samples (n=105) were collected during the dry (June) and rainy (December) season in the estuarine system at 3 stations (,(Piraquê-açu and Piraquê-mirim and confluence). The concentrations of soils and rocks were obtained by pseudototal and partial extractions, in order to compare which constituents are more leachable of these environmental components. The results of the analyzes showed that the latosols originated from gneiss are similar to the dissolved content of the SEPAPM water bodies, with the contribution of the Barrier Group at the mouth during the rainy season. Statistical analysis shows that SEPAPM water bodies are similar independent of rainfall and tide, with only fluctuations in the concentrations of some elements in the water column.